2017
DOI: 10.1111/pai.12746
|View full text |Cite
|
Sign up to set email alerts
|

Impact of solar ultraviolet radiation on atopic dermatitis symptoms in young children: A longitudinal study

Abstract: Atopic dermatitis symptoms in children are likely to be affected by exposure to solar UVR with a cumulative effect, and this effect is different according to season.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Previous studies have also found that psoriasis is less prevalent and less active during the summer [32,33]. One of the main mechanisms is that high temperatures increase UV exposure, resulting in increased vitamin D production [46]. Vitamin D plays a crucial role in regulating dendritic and keratin-forming cells and T-cell proliferation [47].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also found that psoriasis is less prevalent and less active during the summer [32,33]. One of the main mechanisms is that high temperatures increase UV exposure, resulting in increased vitamin D production [46]. Vitamin D plays a crucial role in regulating dendritic and keratin-forming cells and T-cell proliferation [47].…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors may also have an impact on symptoms, including pain and the occurrence of complications such as photosensitivity, deficiencies, the cancer risk and infections. [6][7][8][9][10][11][12] Individual disease burden has already been evaluated in several skin diseases using patient questionnaires such as topic dermatitis, vitiligo hand eczema, haemangioma, inherited ichthyosis, sensitive skin and very recently psoriasis. [13][14][15][16][17] Even though it has become the main focus in the management of dermatological diseases, no methodology allowing the design of patient-oriented burden questionnaires in dermatology has been proposed so far.…”
Section: Introductionmentioning
confidence: 99%